2019
DOI: 10.4034/pboci.2019.191.121
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Saliva Quantity and Content Parameters with Caries Intensity Levels: A Cross-Sectional Study Among Subcarpathian Children

Abstract: Objective: To evaluate saliva quantity and content parameters among children of 7 and 12 years old, who permanently living on the territory of Subcarpathia with the registered territoryassociated fluoride deficiency in the water, and their association with the caries status of pediatric patients. Material and Methods: The study sample was formed of 48 children (22 of 7 years old and 26 of 12 years old). The content of calcium in the oral liquid was determined by the ocresolphthalein complexone method. Estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…However, some studies have reported no relationship between caries activity and salivary flow rates. 12,14 Similar to results reported in published study findings, no statistically significant difference was found regarding the saliva flow rate. However, this result could be attributed to the study group not including patients with systemic salivary gland disease that can cause hyposalivation or xerostomia, but only healthy children who had not used any drugs such as antidepressants, antihistamines, diuretics or narcotics, which can reduce saliva flow, for at least four months.…”
Section: Discussionsupporting
confidence: 86%
“…However, some studies have reported no relationship between caries activity and salivary flow rates. 12,14 Similar to results reported in published study findings, no statistically significant difference was found regarding the saliva flow rate. However, this result could be attributed to the study group not including patients with systemic salivary gland disease that can cause hyposalivation or xerostomia, but only healthy children who had not used any drugs such as antidepressants, antihistamines, diuretics or narcotics, which can reduce saliva flow, for at least four months.…”
Section: Discussionsupporting
confidence: 86%
“…Under the cross-sectional study conditions among children-residents of the Subcarpathian region, authors found that caries intensity levels were more related to the saliva-associated parameters, rather than salivary flow rate [25]. Even though salivary flow rate was not a targeted measurement of present research, we also registered an association between the stabilized pattern of caries intensity and increasing tendency of calcium content within oral fluid.…”
Section: Resultsmentioning
confidence: 47%
“…Produced samples were further analyzed on total level of calcium ions (mmol/l), bound calcium level (mmol/l), free calcium level (mmol/l), phosphate ion level (mmol/l), alkaline phosphate activity (nmol/s-l) and pH [25][26][27]. Those measurements were provided using "Philisit-Diagnostics" diagnostic standard kit (Ukraine) within in-lab conditions by the methodologies (o-cresolphthalein complexone method for calcium level evaluation; phosphoric-molybdic acid recovery method with spectrophotometrical evaluation for phosphate ion level evaluation; immunofluorescent method with Dimension RxL Max Integrated Chemistry System (Siemens Healthineers, Ukraine) for alkaline phosphate activity evaluation; and strip-test for pH evaluation) already described previously [25][26][27]. An overall complex of oral fluid examinations was aimed at its' mineralizing potential objectification with further possible interpretation using obtained numerical data.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Bilyschuk informó que niños de 12 años con bajo riesgo cariogénico presentaron concentración de calcio en saliva de 1.08 0.09 mmol/L. 5 Para potencializar la remineralización del esmalte y disminuir las lesiones cariosas se han adicionado a productos odontológicos compuestos cálcicos, con la finalidad de incrementar la biodisponibilidad de los iones de minerales en la interfaz dentaria. Entre éstos se encuentran el fosfato de calcio amorfo, el fosfato tricálcico y fosfopéptido de caseína-fosfato de calcio amorfo (CPP-ACP).…”
Section: Antecedentesunclassified